EVALUASI MANAJEMEN DATA DAN INFORMASI KESEHATAN PUSKESMAS DI KABUPATEN BELITUNG - , Friyadi Gunawan; , dr. Lutfan Lazuardi, M.Kes, PhD ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The role of health information systems is to generate, analyze and disseminate of health data into information that can be utilizedat the level of health care management, a lot of data needs to see health indicators will be greatly helped by the use of information and communication technologies ranging from the simplest, using word processing and spread sheet applications, until the use of the integrated application such as health management information systems (SIMPUS), information technology can help data processing. In 2007 the health information systems was ever used Bangka Belitung Islands province, Belitung district enlisted the help of Health Management Information System (SIMPUS) in 9 public health care but its implementation suffers failure. The approachof PRISM si used inidentifying the problems and obstacles in the development of health information systems according to technical, organization, and behavior determinant factors. Purpose: To evaluate the performance of management information system of primary health care in Health Office of Belitung District cording to technical, Organization, and behavior determinan factors Methods: Study of eksplorstif descriptive data by questionnaires PRISM (Perfomance Routine Information System Management) from Aqil et al., 2009 to see determinan factors technical, organization and behavior with 9 respondents in the primary health care SP2TP officers. Results: On technical determinant factors obtained the result of value of 2.00. Examination of the accuracy of the data average value of 6,00 delivery processing and analysis of data average value of 8,33 and supporting hardware equipment of SIK obtained results 19 PC Computer, internet access, 8 backup data, 19 printers, 2 generators, organizational determinant factors obtained the value of governance (0), planning (3.70), supervision (51,85) and financing (0). Determinant factors of behaviors how the results indicate the ability of a data quality assessment (77,8) problem-solving related to SIK (58.9) HIS officer's competency SIK (57,1) and HIS officerâs motivation (73.0) Conclusion: Public Health Care with the good category has been been ready in the implementation of management data and health information system according to technical, Organization and behavior as for Public Health Care with enoug handless category has been ready to behavior determinan factor.